Improved accuracy of GTEM Cell/SAC-correlated measurement of IC-radiated electric fields by a correction factor - Chua, King Lee (2015)
Gigahertz Transverse Electromagnetic (GTEM) cell has been a popular test facility for evaluating integrated circuit (IC)- radiated emission. Since it is single-port test device, GTEM measurement cannot distinguish electric field component from magnetic field component. Rather, both fields are captured as a global quantity. It is therefore speculated that radiated emission measured using GTEM cell is less precise comparing with near-field probe scanning technique. Nonetheless, GTEM cell is cost-effective in providing sufficiently good ambient shielding to conduct field measurement at broad frequency range. Meanwhile, GTEM measurement typically is associated with semi-anechoic chamber (SAC) measurement. This study attempted to improve the correlation between GTEM and SAC through a correction factor. A specific circuitry pattern was constructed to replicate the wide-ranging IC interconnections and used for evaluation in GTEM cell and SAC. The horizontal and vertical electric fields based on GTEM measurement were preprocessed by MATLAB code to obtain the correction factor. Subsequently, the correction factor was employed to fine-tune any deviation arose from correlating the IC-radiated electric fields of GTEM cell to SAC. The results demonstrated a strong correlation coefficient upon regulation of GTEM fields with a correction factor, thereby offering a high-accuracy GTEM cell measurement strategy.